Effects of Stretching and Proprioceptive Training on Craniovertebral Angle and Suboccipital Muscle Tone in Individuals with Forward Head Posture - Gim, Mina; Ahn, Ilhwan; Kim, Nyeonjun; Koo, Japung; Lee, Muyeol; Lee, Seonghwan; Kim, Yongyoun (Journal of International Academy of Physical Therapy Research, 2025)
Background: The progressive digitalization of contemporary life, coupled with prolonged sedentary behavior, has contributed to the widespread occurrence of forward head posture (FHP) in the general population. Among the various exercise interventions aimed at correcting FHP, stretching exercises and proprioceptive training have garnered significant attention. Objectives: To investigate the effects of stretching exercises and proprioceptive training on craniovertebral angle (CVA), an indicator of forward head posture (FHP), and on the muscle tone of the suboccipital muscles. Design: Randomized controlled trial. Methods: Thirty participants were randomly assigned to either the stretching exercise group (n=15) or the proprioceptive training group (n=15), and each group underwent intervention three times per week for six weeks. CVA and muscle tone of the suboccipital muscles were measured before and after the six-week intervention, and the results were statistically analyzed for comparison. Results: Both groups showed a significant increase in CVA after the intervention (P<.05), with no significant difference between the groups. The muscle tone of the suboccipital muscles did not show statistically significant changes either within or between the groups. Conclusion: Six weeks of stretching exercise and proprioceptive training both resulted in a significant increase in CVA, demonstrating that both interventions are effective in improving FHP. However, neither intervention produced significant changes in the muscle tone of the suboccipital muscles.